Nitrogen Addition to the Shielding Gas for Welding Hyper-duplex Stainless Steel - Pimenta,André Rocha (2020)
Abstract: In the present work we have studied the effects of nitrogen addition on the equilibrium of the volume fraction ratio austenite/ferrite and on the structural properties of weldments produced by gas tungsten arc welding (GTAW). The welded joints in tubes UNS S32707 of hyper-duplex steel were produced using argon and nitrogen gas welding, with nitrogen added in ratios of 1.5, 2.5, 3.5, 4.5, and 5.5%. Microstructural characterization of this material under the different processing condition was conducted by means of optical microscopy, scanning electron microscopy, local chemical analysis by X-ray energy dispersive spectroscopy, electron backscatter diffraction Vickers microhardness test, and digital image processing. All welding conditions resulted in welded joints with equiaxial grains microstructure containing austenite both at the boundaries and in the ferrite matrix. Microhardness measurements did not show significant variation in relation to the base metal. The use of welding gases with higher percentages of nitrogen resulted in increases in the austenite volume fraction in the order of 39 to 57% when considering the nitrogen content ranging from 1.5 to 5.5%.